Intellectual property protection in distance education system - Bukhkalo, S. I.; Ageicheva, Anna; Komarova, Oleksandra; Babash, Larysa (НТУ "ХПИ", 2018)
Main aspects of intellectual property protection in the implementation of distance learning are studied. The relevance based on the need of implementation distance learning and the use of the opportunities offered by e-learning. The problem of the protection intellectual property in distance education. It is determined that technical means should provide a program of students' work on the content of the educational material (program of its learning process), a combination of training and education functions, strengthening the control and self-control of the process and its results of the process of learning knowledge, assistance in implementing the ideas of differential and problem learning.

В работе рассматриваются основные аспекты защиты интеллектуальной собственности при внедрении дистанционного обучения. Актуальность работы обусловлена необходимостью внедрения дистанционного обучения и использованием возможностей, которые дает электронное обучение. Исследована проблема необходимости защиты интеллектуальной собственности в системе дистанционного образования. Установлено, что технические средства должны обеспечивать программу работы студентов по содержанию учебного материала (программа его учебного процесса), сочетание функций обучения и образования, укрепление контроля и самоконтроля процесса и его результатов процесса обучения знаниям, помощи в реализации идей дифференциального и проблемного обучения
Защита интеллектуальной собственности в системе дистанционного образования
Keywords: distance education; e-learning; adult life long education; intellectual property; электронное обучение; непрерывное образование взрослых; интеллектуальная собственность